2016
DOI: 10.1242/jeb.149880
|View full text |Cite
|
Sign up to set email alerts
|

Impact damage and repair in shells of the limpet Patella vulgata

Abstract: Experiments and observations were carried out to investigate the response of the Patella vulgata limpet shell to impact. Dropped-weight impact tests created damage that usually took the form of a hole in the shell's apex. Similar damage was found to occur naturally, presumably as a result of stones propelled by the sea during storms. Apex holes were usually fatal, but small holes were sometimes repaired, and the repaired shell was as strong as the original, undamaged shell. The impact strength (energy to failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…However, these studies have focused primarily on relatively high forces (≥65% of the one-time breaking force) and relatively low cycle numbers (mostly <1000), as they have considered fatigue in the context of predation. A few studies have also examined how repeated impacts damage mollusk shells (Crane et al, 2018;Taylor, 2016), but again, these have focused on a few, high-force impacts (<120 impacts). None of this research has developed a broader framework to examine how a wide range of potentially fatiguing forces affects animal survival.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies have focused primarily on relatively high forces (≥65% of the one-time breaking force) and relatively low cycle numbers (mostly <1000), as they have considered fatigue in the context of predation. A few studies have also examined how repeated impacts damage mollusk shells (Crane et al, 2018;Taylor, 2016), but again, these have focused on a few, high-force impacts (<120 impacts). None of this research has developed a broader framework to examine how a wide range of potentially fatiguing forces affects animal survival.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why some limpets were unable to repair holes even after long periods. Similarly, the apex seems to act as a sacrificial point in the shell [17], absorbing most of the damage. This is remarkably similar to 'crumple zones' in cars, a structural safety mechanism that serves to absorb, like the apex, energy in an impact, preserving more important structures within.…”
Section: Discussionmentioning
confidence: 99%
“…After inflicting damage, and waiting for a chosen repair period, the limpets were removed from the rocks using sharp knives, before removing the animal inside and cleaning the shell and storing it for subsequent testing. In a previous study [17], we devised a method of impact testing which was also used here (see below). We found that the energy required to cause failure when the shell was impacted on its apex was related to the size of the shell raised to the power of 4.6 [17].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Predators often attack certain regions of the shell or apply other behaviors such as peeling or impacting, which are not captured in the typical two-plate test. Using multiple methods to quantify strength of the limpet Patella vulgata, Taylor (2016) demonstrated differences between the impact strength, quantified by dropping rods onto shells, and the strength as measured with a more traditional two-plate crushing test.…”
Section: Introductionmentioning
confidence: 99%